PHILOSOPHICAL HERMENEUTICS - B. Chethimattam, John (Journal of Dharma, 1980)
Hermeneutics has only a remote connection with the name of the god Hermes, the divine messenger who announces the decision of the gods. Even so, recognizing the connection Plato calls the poets hermenes ton theon, the interpreters of gods as opposed to the bards who were merely interpreters of interpretations. Hermeneutics is primarily a search for meaning. Taking it in this sense, Aristotle called his treatise on linguistic expression or theory of statement, Peri hermeneias. Since the 16th century, in Protestant circles, heremeneutics was developed into an independent discipline for formulating universally valid rules of interpreting Scripture in opposition to the Tridentine and post-Tridentine Catholic claim concerning the unique prerogative of the Church in the matter.